Urgensi Latihan Mengulang dalam Belajar Bahasa Arab - Luqman Luqman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Repeating is a practical way of learning by doing the same thing repeatedly and earnestly with the guidance of faculty or independently, an association aiming to strengthen or enhance a skill to the fullest with a short path. This method has many advantages compared with other methods, which are in relatively short time and quickly obtainable mastery and skill to be expected, the students will have the knowledge ready and strong, and more importantly is the learners inculcate the habit of regular study, discipline and mandiri.Metode and repeat this exercise is very suitable for learning the Arabic language, because it has the same karakeristik denagan learning the Qur'an, hadith and other Islamic sciences.